Association between relative fat mass and risk of arthritis: a study based on populations in China and the United States - Yang, Yang; Li, Yuanfan; Shui, Ruixing; Li, Dapeng (Frontiers in Nutrition, 2025)
This study examined the association between relative fat mass (RFM) and the prevalence of arthritis in two distinct populations: one from China and the other from the United States. The findings indicated a non-linear relationship between RFM and the development of arthritis. A robust positive correlation was identified in the US male population, while no such correlation was observed in the Chinese male population. In the American female population, a non-linear correlation was observed between RFM and arthritis, with elevated RFM below the threshold of 35.85 exhibiting a modest decrease in the risk of arthritis, and elevated RFM above the threshold demonstrating a substantial increase in the risk of arthritis. A similar trend was observed in Chinese women; however, the protective effect was not significant below the threshold (p > 0.05). Subgroup analyses further revealed that factors such as hypertension and smoking significantly altered the association between RFM and arthritis in the US population of both genders, whereas the relationship between RFM and arthritis was relatively stable in the Chinese female population. The present study suggests that increased RFM is associated with the prevalence of arthritis in men, and that maintaining optimal levels of RFM may reduce the risk of arthritis in women. RFM, as a new independent arthritis risk factor, can be used for screening and long-term monitoring of patients with arthritis, as well as to assess the effectiveness of various treatment modalities.